Contract Teaching and Oral Exam: What Do The Teacher Candidates Think? - Yıldıray Karadağ; Mücahit Aydoğmuş; Alper Kesten (Anı Publishing, 2020)
The purpose of this study is to examine the opinions of teacher candidates about contract teaching and oral exam system. The study group consisted of 12 teacher candidates involved in different departments of the faculty of education. The criterion sampling method was used to determine the participants, and interviews conducted with the participants who met the criteria. A semi-structured interview form used as a data collection tool and, a thematic analysis method was realized to analyze the data. Results revealed that teacher candidates regarded contracted teaching as it is harming the teaching profession, making teachers uneasy because there is no job guarantee and as a profession, and they were found to be more insecure and riskier than before. It concluded that the six-year compulsory service period affects teachers' personal life negatively. Lack of teachers' right to replacement is also a problem. They also stated that the oral exam cannot be objective and that the chance factor may be effective. Based on the opinions of the participants, arrangements can be made by the authorized institutions for contract teaching and oral examination system. Besides, to reduce the negative thoughts of pre-service teachers, it can be explained to pre-service teachers why contract teaching and oral examination are important.